Ionizing radiation, cerebrovascular disease, and consequent dementia: A review and proposed framework relevant to space radiation exposure - Miller, Kathleen B.; Mi, Kaitlyn L.; Nelson, Gregory A.; Norman, Ryan B.; Patel, Zarana S.; Huff, Janice L. (Frontiers in Physiology, 2022)
Space exploration requires the characterization and management or mitigation of a variety of human health risks. Exposure to space radiation is one of the main health concerns because it has the potential to increase the risk of cancer, cardiovascular disease, and both acute and late neurodegeneration. Space radiation-induced decrements to the vascular system may impact the risk for cerebrovascular disease and consequent dementia. These risks may be independent or synergistic with direct damage to central nervous system tissues. The purpose of this work is to review epidemiological and experimental data regarding the impact of low-to-moderate dose ionizing radiation on the central nervous system and the cerebrovascular system. A proposed framework outlines how space radiation-induced effects on the vasculature may increase risk for both cerebrovascular dysfunction and neural and cognitive adverse outcomes. The results of this work suggest that there are multiple processes by which ionizing radiation exposure may impact cerebrovascular function including increases in oxidative stress, neuroinflammation, endothelial cell dysfunction, arterial stiffening, atherosclerosis, and cerebral amyloid angiopathy. Cerebrovascular adverse outcomes may also promote neural and cognitive adverse outcomes. However, there are many gaps in both the human and preclinical evidence base regarding the long-term impact of ionizing radiation exposure on brain health due to heterogeneity in both exposures and outcomes. The unique composition of the space radiation environment makes the translation of the evidence base from terrestrial exposures to space exposures difficult. Additional investigation and understanding of the impact of low-to-moderate doses of ionizing radiation including high (H) atomic number (Z) and energy (E) (HZE) ions on the cerebrovascular system is needed. Furthermore, investigation of how decrements in vascular systems may contribute to development of neurodegenerative diseases in independent or synergistic pathways is important for protecting the long-term health of astronauts.